Influence of cannonball tree (Couroupita guianensis Aubl.) leaf extract and electrolyzed oxidizing water on postharvest quality of tomato - Farzana Islam; Prosanta Dash; Shimul Das (Journal of Horticulture and Postharvest Research, 2023)
Purpose: Managing postharvest losses to extend shelf life and cut down on waste is of paramount importance nowadays, especially when resources are scarce. Extracts from the leaves of the cannonball tree and electrolyzed oxidizing water were employed to improve postharvest handling procedures. Research method: The experiment consisted of cannonball tree leaf extracts (5 ml/L, 10 ml/L, 15 ml/L, 20 ml/L) and two pH levels of electrolyzed oxidizing water (pH 3, pH 5). Tomato treated with distilled water was considered as a control. The experiment was conducted as a Completely Randomized Design under a factorial arrangement with three replications. Findings:  Cannonball tree leaf extracts (10 ml/L) significantly retained acceptable fruit color, firmness, high level of titratable acidity, flavonoid, carotenoid, anthocyanin, vitamin C, IC50 and prolonged shelf life by more than three days over other treatment combinations. Compared to untreated fruit, treated fruit decayed at a slower rate (30.7 0.4%) and lost less weight (35.4 0.7%). Additionally, electrolyzed oxidizing water (pH 5) significantly outperformed alternative postharvest management techniques to lower postharvest losses, IC50 (121.6 2.1 mg/Kg) activity, enhancing titratable acidity and vitamin C content, and other physico-chemical attributes and thereby increasing tomato shelf life by more than two days. Research limitations: No limitations were encountered. Originality/Value: Electrolyzed oxidizing water (pH 5) or cannonball tree leaf extract (10 ml/L) appears to be the most promising sustainable solution for reducing postharvest tomato losses.